Intra-gastric balloon associated with acute pancreatitis - Chirinos Vega, Juan Antonio (2023)
We present a clinical case of a young woman with the habit of sleeping in the prone position. She reports that after intragastric balloon placement, she begins with nocturnal episodes of epigastric abdominal pain. The most recent episode was characterized by sudden and intense abdominal pain, elevation of pancreatic enzymes, and imaging findings compatible with acute pancreatitis. After carrying out a systematic approach, other potential causes were ruled out. After removing the intragastric balloon, immediate cessation of the nocturnal episodes of pain was obtained. The etiology was attributed to the mechanical compression phenomena caused by the balloon on the pancreatic body during rest in the prone position. We note that the habit of resting in the prone position would constitute a potential risk factor for acute pancreatitis after intragastric balloon placement, so this factor should be considered when counselling candidates for this technique.